Prostaglandin D2 and leukotriene E4 synergize to stimulate diverse TH2 functions and TH2 cell/neutrophil crosstalk. - Xue, L; Fergusson, J; Salimi, M; Panse, I; Ussher, J; Hegazy, A; Vinall, S; Jackson, D; Hunter, MG; Pettipher, R; Ogg, G; Klenerman, P (Elsevier, 2015)
BACKGROUND: Prostaglandin D2 (PGD2) and cysteinyl leukotrienes (cysLTs) are lipid mediators derived from mast cells, which activate TH2 cells. The combination of PGD2 and cysLTs (notably cysteinyl leukotriene E4 [LTE4]) enhances TH2 cytokine production. However, the synergistic interaction of cysLTs with PGD2 in promoting TH2 cell activation is still poorly understood. The receptors for these mediators are drug targets in the treatment of allergic diseases, and hence understanding their interaction is likely to have clinical implications. OBJECTIVE: We aimed to comprehensively define the roles of PGD2, LTE4, and their combination in activating human TH2 cells and how such activation might allow the TH2 cells to engage downstream effectors, such as neutrophils, which contribute to the pathology of allergic responses. METHODS: The effects of PGD2, LTE4, and their combination on human TH2 cell gene expression were defined by using a microarray, and changes in specific inflammatory pathways were confirmed by means of PCR array, quantitative RT-PCR, ELISA, Luminex, flow cytometry, and functional assays, including analysis of downstream neutrophil activation. Blockade of PGD2 and LTE4 was tested by using TM30089, an antagonist of chemoattractant receptor-homologous molecule expressed on TH2 cells, and montelukast, an antagonist of cysteinyl leukotriene receptor 1. RESULTS: PGD2 and LTE4 altered the transcription of a wide range of genes and induced diverse functional responses in TH2 cells, including cell adhesion, migration, and survival and cytokine production. The combination of these lipids synergistically or additively enhanced TH2 responses and, strikingly, induced marked production of diverse nonclassical TH2 inflammatory mediators, including IL-22, IL-8, and GM-CSF, at concentrations sufficient to affect neutrophil activation. CONCLUSIONS: PGD2 and LTE4 activate TH2 cells through different pathways but act synergistically to promote multiple downstream effector functions, including neutrophil migration and survival. Combined inhibition of both PGD2 and LTE4 pathways might provide an effective therapeutic strategy for allergic responses, particularly those involving interaction between TH2 cells and neutrophils, such as in patients with severe asthma.